A late harvest: post '94 policy & its implications in the Hex River Valley - Steyn, Lisa (My University, 2016)
This report presents research into policy implications in the Hex River Valley in the Western Cape Province. The research aims to understand how key policy interventions introduced by the democratic national government have performed over the past 20 years in this specific geographic area. The policy examined relate specifically to of agriculture, labour, housing, land reform, black economic empowerment, and substance abuse. The findings show mixed results. Some policy has gone a long way in improving the lives of people in the valley. In other instances it has been woefully inadequate. Often, policy is simply unable to keep up with the changing landscape and the new problems that continue to develop. All the while the table grape industry at the heart of this settlement has proved to be incredibly flexible in adapting. This report consists of two sections. The first is a long-form journalistic piece presenting the research and its findings in a narrative writing style which is intended to engage the reader. The second section is the scholarly methods document sets out the academic research supporting this work. It also analyses on the manner in which the research was conducted and the reasons therefore.
Keywords: Communication in economic development; Mass media--Political aspects--South Africa; Table grapes--Economic aspects--South Africa; Grapes--Research--South Africa; Evaluation research (Social action programs)--South Africa